2019
DOI: 10.1017/s0033291718003835
|View full text |Cite
|
Sign up to set email alerts
|

Group rumination-focused cognitive-behavioural therapy (CBT) v. group CBT for depression: phase II trial

Abstract: BackgroundAlthough cognitive-behavioural therapy (CBT) is an effective treatment for depression, less than half of patients achieve satisfactory symptom reduction during treatment. Targeting known psychopathological processes such as rumination may increase treatment efficacy. The aim of this study was to test whether adding group rumination-focused CBT (RFCBT) that explicitly targets rumination to routine medical management is superior to adding group CBT to routine medical management in treating major depres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(38 citation statements)
references
References 36 publications
1
36
1
Order By: Relevance
“…However, the indirect effects in the structural equation model showed that that kind of rumination, when used to think and talk about past events, can have a positive mood-enhancement effect. Although previous research has shown that concrete rumination can be used to reduce depression [43], the current results suggest that abstract rumination may be used to gain insight about experiences needed for planning for present and future behaviors (directive function) and communication/sharing with others (social function). However, these results must be taken with caution as participants in the current study were not drawn from a clinical population and so may differ in the contents and duration of rumination as compared to clinical groups.…”
Section: Plos Onecontrasting
confidence: 73%
“…However, the indirect effects in the structural equation model showed that that kind of rumination, when used to think and talk about past events, can have a positive mood-enhancement effect. Although previous research has shown that concrete rumination can be used to reduce depression [43], the current results suggest that abstract rumination may be used to gain insight about experiences needed for planning for present and future behaviors (directive function) and communication/sharing with others (social function). However, these results must be taken with caution as participants in the current study were not drawn from a clinical population and so may differ in the contents and duration of rumination as compared to clinical groups.…”
Section: Plos Onecontrasting
confidence: 73%
“…Unfortunately, it is unclear whether existing interventions can successfully improve rumination (Watkins, 2015). A recently developed intervention, Rumination‐Focused Cognitive Behavioral Therapy (RFCBT), showed its efficacy for depressive patients but requires twelve sessions to complete (Hvenegaard et al, 2020; Watkins et al, 2011). CBT requires patients to be conscious of their maladaptive ruminative thinking, so then they will be able to learn how to control it.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it may be useful to visualize one's internal state of mind outside of one's awareness and to use that information to facilitate one's self‐control. Also, these studies investigating the efficacy of RFCBT (Hvenegaard et al, 2020; Watkins et al, 2011) were not designed to determine what aspect of RFCBT contributes to reducing ruminations. Thus, it is necessary to identify and determine any underlying brain dysfunctions related to rumination.…”
Section: Introductionmentioning
confidence: 99%
“…Rumination-focused cognitive behaviour therapy (RfCBT) was designed to teach patients how to interrupt the mental habit of rumination, and to shift into a more constructive style of thinking, characterized by more concrete and experiential processing. In clinical trials, RfCBT has been shown to reduce depression and prevent relapse in medication-refractory residual depression (Watkins et al, 2011) when added to anti-depressant medication, and in depressed patients relative to CBT (Hvenegaard et al, 2019). However, to date, RfCBT has not been investigated in patients who are currently experiencing a chronic episode of major depression, lasting longer than 1 year that has not responded to at least two trials of anti-depressant medication.…”
Section: Introductionmentioning
confidence: 99%